2014
DOI: 10.5713/ajas.2014.14435
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetic Diversity, Relationships and Structure among Korean Native Cattle Breeds Using Microsatellite Markers

Abstract: Four Korean native cattle (KNC) breeds—Hanwoo, Chikso, Heugu, and Jeju black—are entered in the Domestic Animal Diversity Information System of the United Nations Food and Agriculture Organization (FAO). The objective of this study was to assess the genetic diversity, phylogenetic relationships and population structure of these KNC breeds (n = 120) and exotic breeds (Holstein and Charolais, n = 56). Thirty microsatellite loci recommended by the International Society for Animal Genetics/FAO were genotyped. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 25 publications
7
25
0
Order By: Relevance
“…; Suh et al . ). Brown Hanwoo is widely used for breeding in Korea, Brindle Hanwoo is from the Korean Peninsula and Jeju Black is from Jeju Island (Fig.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…; Suh et al . ). Brown Hanwoo is widely used for breeding in Korea, Brindle Hanwoo is from the Korean Peninsula and Jeju Black is from Jeju Island (Fig.…”
mentioning
confidence: 97%
“…The other reason is that Brown Hanwoo was selected as the main breed early in the genetic improvement program, whereas Brindle and Jeju Black were excluded (Suh et al . ).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Number of alleles in the remaining seats was between 8 and 14, Dominant alleles of 13 Chinese and foreign breeds were mainly composed of ILSTS011, INRA035 and ILSTS005. Suh et al (2014) reported that a total of 276 alleles were detected at 30 microsatellite loci across four Korean native cattle breeds (Hanwoo, Chikso, Heugu, and Jeju black). The total number of alleles per locus ranged from 4 (ILSTS005) to 17 (TGLA122), with a mean of 9.20±0.58 alleles.…”
Section: Allelic Distribution and Private Allelementioning
confidence: 99%
“…Worldwide, cattle (Bos taurus) have been economically and culturally important farm animal species since their domestication. Many studies have assessed the diversity of cattle in Asia (Sharma et al, 2016;Nishimaki et al, 2013;Shah et al, 2013), Europe (Mateus et al, 2004;Maudet et al, 2002;Di et al, 2018), Africa (Dadi et al, 2008;Edea et al, 2015), and South America (Acosta et al, 2013;Brasil et al, 2013;Piccoli et al, 2014) and in cattle native to Korea (Suh et al, 2014). In recent years, several microsatellite studies on diversity in Chinese cattle have been published (Yang et al, 2016;Wang et al, 2015;Lou et al, 2006;Han et al, 2006;Li et al, 2007).…”
Section: Introductionmentioning
confidence: 99%